Materials Science and Condensed-Matter Physics: international conference: dedicated to the 60th anniversary from the foundation of the Institute of Applied Physics, October 1-4 Chisinau 2024. Book of abstracts - (:unkn) unknown (CEP USM, 2024)
This book includes abstracts of the communications presented at the 10th International Conference on Materials Science and Condensed-Matter Physics (MSCMP) held in Chisinau, the Republic of Moldova.Until 2018, the MSCMP conference was a traditional biennial meeting organized by the Institute of Applied Physics (IAP) of the Academy of Sciences of Moldova. Unfortunately, due to the COVID pandemic and then the unexpected complication of the political situation in our region, which shook the whole scientific community, the organization of the 10th edition of the MSCMP conference was postponed for 4 long years. At the same time, it is in this year, 2024, that the IAP, which, along with other research institutes of Moldova, currently affiliated with Moldova State University, celebrates its 60th anniversary, to which the 10th edition of the MSCMP conference is dedicated.The aim of this event is two–fold. First, it provides a nice opportunity for discussions and the dissemination of the latest results on selected topics in materials science, condensed-matter physics, and electro-physical and electro-chemical methods of materials treatment. On the other hand, this is an occasion for sketching a broad perspective of scientific research and technological developments for the participants through oral and poster presentations.